2-Methoxyestradiol prevents monocyte adhesion to vascular endothelial cells via downregulation of VCAM-1 expression. (2nd July 2016) - Zhang, Yongfu; Li, Ping; Gao, Qi; Simoncini, Tommaso; Fu, Xiaodong
Abstract: 2-Methoxyestradiol (2-ME) reduces atherosclerotic lesion formation. However, the underlying mechanisms remain largely unknown. In this work, we investigated the effect of 2-ME on monocyte adhesion to vascular endothelial cells. Lipopolysaccharides (LPS) greatly increased the attachment of monocyte onto cultured human umbilical vascular endothelial cells (HUVECs), which was inhibited by 2-ME in a dose- and time-dependent manner, or by the vascular cell adhesion protein-1 (VCAM-1) neutralizing antibody, suggesting that a functional releationship between 2-ME and VCAM-1 may exist. In accordance with this, treatment with 2-ME (10 − 7 –10 − 5 M) for 6–48 h downregulated VCAM-1 protein expression. Meanwhile, the nuclear factor κ B (NF- κ B) p65 subunit activity and its nuclear translocation was inhibited by 2-ME in HUVECs. The PI3K inhibitor wortmannin or the specific Akt siRNA both inhibited the effects of 2-ME, suggesting that 2-ME inhibited p65 activity via PI3K/Akt signaling. In conclusion, 2-ME inhibits VCAM-1 expression and thus prevents monocyte adhesion to vascular endothelial cells via regulation of PI3K/Akt and NF- κ B signaling. These findings will be helpful for better understanding the mechanisms through which 2-ME improves endothelial function.